PERANCANGAN BAHAN PELATIHAN BERBASIS WEBSITE DI KEJURUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI BALAI BESAR PENGEMBANGAN LATIHAN KERJA BEKASI - Riza, Faizal; Hendrakusuma, Dannie Febrianto; Setiabudi, Rachmat; Birowo, Anindito Kusumo; Hidayat, Cahyono Koerniawan (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2023)
Â AbstractBalai Besar Pengembangan Latihan Kerja (BBPLK) Bekasi is a training place for government-owned skills or expertise under the auspices of the Ministry of Manpower headed by Echelon II government officials. In the Center for Job Training Development (BBPLK) Bekasi, there are various kinds of vocational training, one of which is the Information and Communication Technology Vocational School. In the Information and Communication Technology (ICT) Vocational School there are 5 (five) training programs, namely: Graphic Design, Motion Graphic Artist, Network Professional, Mobile Programming and IT Software For Business Solution. In this vocational school, they still use the manual method in processing data on training materials stored in the warehouse. The method used is by filling out the training material expenditure form, then the form is stored in their respective archive folders. This system has been running well but still has weaknesses, including if the admin is asked to find training material data quickly, the admin will have difficulty finding one by one archive that has been stored and takes a long time and taking training materials that are not in accordance with the training program and possibly there is a missing file. The research method uses data collection by means of observation, interviews and literature study. So with the design of a website-based training material inventory information system, it can make it easier to find data on the availability of training materials according to the training program and make the work process of checking training materials more effective and efficient.Â Keywords : training materials, system, information, inventory, website..